Kurdish EFL Students’ Perceptions about the use of E-learning During the Covid-19 Lockdown (Raparin Journal of Humanities (RJH), 2022)
The outbreak of the coronavirus (Covid-19) in December 2019 caused the total closure of educational institutions and led to stop of the face-to-face teaching for a long time. Therefore, e-learning was applied as an alternative teaching method to continue education. However, little is known about students’ perceptions on the use and acceptance of e-learning implemented during the Covid-19 lockdown, especially in the Kurdistan region of Iraq. Hence, this study aims to explore the university students’ perceptions about the use of e-learning during the lockdown in the Kurdistan region of Iraq. In so doing, a mixed-method approach is utilised to collect both quantitative and qualitative data from 50 Kurdish EFL students. The results of data analysis revealed that more students show positive perceptions than those who hold neutral and negative perceptions about the use of e-learning during the lockdown.